Understanding Spatial and Temporal Tensions of Iranian Immigrant Caregiver-employees for Home Environment Design Improvement - Akbari, Zahra (My University, 2018)
The growing number of seniors in Canada and worldwide has highlighted the significant role of people providing unpaid care to their loved ones, who are so-called “family caregivers”. A great number of family caregivers are employees working in the paid labor market, who experience additional difficulties as a result of multiple responsibilities in their daily lives. This group of caregivers has to cope with continuous work-related tensions in addition to their daily caregiving burdens. In multicultural nations such as Canada, a great number of caregiver-employees also belong to the immigrant community. While immigrant caregiver-employees (CEs) are faced with extra challenges compared to other CEs, limited research is available for this underrated and overlooked population. This group of CEs have the challenging task of working from home while providing intensive care for their loved one. Therefore, the home environment is an everyday space highly susceptible because of daily spatial and temporal tensions. The current research aims to explore the experience and tensions of Iranian immigrant caregiver-employees in order to assist them in managing their ever-growing responsibilities in the home environment by providing a set of specific home modification strategies. Initially, CEs major tensions and management strategies are identified by in-depth qualitative interviews. A novel Photovoice methodology is implemented to illustrate these tensions exclusively through self-captured photos. Five major themes are identified for the tensions, which are categorized as: (i) personal, (ii) caregiving, (iii) spatial, (iv) family and social, and (v) temporal tensions. The management strategies utilized by caregivers to cope with these tensions are also organized into five additional themes: (i) spatial, (ii) personal, (iii) social, (iv) monitoring and control, and (v) assistive and supportive strategies. Although, these management strategies are effective in resolving some of the tensions, specific tensions remain unmanaged for immigrant CEs’. Unmanaged tensions are analyzed under the therapeutic landscape framework to improve CEs’ health and well-being. A comprehensive list of architectural home modification strategies is proposed to relieve CEs’ tensions in the home environment. Finally, an ideal home is pictured for Iranian immigrant CEs, considering their most significant spatial, natural, symbolic and social requirements. The outcomes of the current research will assist immigrant CEs in managing their daily tensions while performing their working and caregiving responsibilities. The proposed home modification strategies will minimize CEs’ tensions to a large scale, improve their level of mental and physical health, and increase their quality of life. Furthermore, the current research results in increased safety and independence for the care recipients.
Keywords: immigrants; caregiver-employees; spatial and temporal tensions; home environment; Photovoice